Evaluation of the efficacy and safety of original filgrastim (Neupogen®), biosimilar filgrastim (Leucostim®) and Lenograstim (Granocyte®) in CD34+ peripheral hematopoietic stem cell mobilization procedures for allogeneic hematopoietic stem cell transplant donors. Issue 3 (June 2016) - Sivgin, Serdar; Karakus, Esen; Keklik, Muzaffer; Zararsiz, Gokmen; Solmaz, Musa; Kaynar, Leylagul; Eser, Bulent; Cetin, Mustafa; Unal, Ali
Abstract: Objectives and Aim: In this study, we aimed to compare the potency of different G-CSF agents including original filgrastim (Neupogen®), biosimilar filgrastim (Leucostim®) and Lenograstim (Granocyte®) on CD34 + cell mobilization in patients that underwent allogeneic hematopoietic stem cell transplantation (alloHSCT). Patients and Methods: The data of 243 donors for alloHSCT recipients diagnosed with mostly acute leukemia and myelodsyplastic syndromes (MDS) were analyzed, retrospectively. Data for stem cell mobilization have been recorded from patients' files. Donors who received Filgrastim (Neupogen®, Group I), biosimilar Filgrastim (Leucostim®, Group II) and Lenograstim (Granocyte®, Group III) were analyzed for total CD34 + cell count at the end of mobilization procedures. Results: A total of 243 donors and patients for alloHSCT were analyzed retrospectively. The diagnosis of the patients were; acute myeloid leukemia (AML) (110 patients, 45.2%), acute lymphoid leukemia (ALL) (61 patients, 25.1%), aplastic anemia (AA) (38 patients, 15.6%), lymphomas (14 patients, 5.7%) and others (20 patients, 8.4%). The median number of total collected PB CD34 + cells (×10 6 /kg) was 7.12 (min–max: 5.38–7.90) in the Neupogen® group, 7.27 (min–max: 6.79–7.55) in the Leucostim® group and 7.15 (min–max: 5.34–7.58) in the Granocyte® group. There was no statistically significant difference among groups in terms of total collected PB CD34 + cells (p = 0.919). The median doses of G-CSF agents (µg/kg/day) in PBSC collection in Neupogen® group was; 11.00 (10.00–12.00) in Leucostim® group10.35 (min–max: 10.00–11.10) and in Granocyte® group11.00 (min–max: 10.00–11.00). There was no statistical significance among groups (p = 0.215). Conclusion: Biosimilar filgrastim (Leucostim®) was found comparable to original Filgrastim (Neupogen®) and Lenograstim (Granocyte®) for PBSC mobilization in donors of the patients that underwent alloHSCT.